MODEL KURIKULUM PENDIDIKAN AGAMA ISLAM DI SDIT AL-ANWAR DAN FIRDAUS MOJOKERTO JAWA TIMUR - Lilam Kadarin Nuriyanto (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This research is conducted in SDIT Al Anwar and SDIT Firdaus Mojokerto, East Java. This research is to identify the model of the Islamic education curriculum, to indicate the religious educational implementation, to identify and understand the current difficulties, and finding the ideal model for the religious educational curriculum and its implementation in forming the students’ character. The currently operating model of thecurriculum is concerned with the National education curriculum’s development which is adapted to each condition of the schools. This also involves local content and self-individual development from the students. The development from the institution is referred to the Quran, Al-Islam, the history of Islam, and Arabic language. The everyday routine of reading prayers, the Quran, brief religious lectures, memorizing the brief verses (the 30th), etc is also introduced. The implementation adapts from two learning thematic models; the lower class, and integrated with the upper class. The school applies a full day learning method. The strongest distinction possessed by the two local curriculum and self-individual development SDIT is located by their ability in cooperating each other in order to create a leadership figure such as the prophet Muhammad saw; trustworthy, fatonah, and tablig. On the other hand, the unfinished and incomplete process of property construction has become a main problem. The ideal curriculum model which has been implemented becomes energy between cultures both in schools and environments.